Value of upper gastrointestinal endoscopy for gastric cancer surveillance in patients with Lynch syndrome. Issue 1 (13th October 2020) - Ladigan‐Badura, Swetlana; Vangala, Deepak B.; Engel, Christoph; Bucksch, Karolin; Hueneburg, Robert; Perne, Claudia; Nattermann, Jacob; Steinke‐Lange, Verena; Rahner, Nils; Schackert, Hans K.; Weitz, Jürgen; Kloor, Matthias; et al.
Abstract: In our study, we evaluated the effectiveness of upper gastrointestinal (GI) endoscopy as an instrument for early gastric cancer (GC) detection in Lynch syndrome (LS) patients by analyzing data from the registry of the German Consortium for Familial Intestinal Cancer . In a prospective, multicenter cohort study, 1128 out of 2009 registered individuals with confirmed LS underwent 5176 upper GI endoscopies. Compliance was good since 77.6% of upper GI endoscopies were completed within the recommended interval of 1 to 3 years. Forty‐nine GC events were observed in 47 patients. MLH1 (n = 21) and MSH2 (n = 24) mutations were the most prevalent. GCs in patients undergoing regular surveillance were diagnosed significantly more often in an early‐stage disease (UICC I) than GCs detected through symptoms (83% vs 25%; P = .0231). Thirty‐two (68%) patients had a negative family history of GC. The median age at diagnosis was 51 years (range 28‐66). Of all GC patients, 13 were diagnosed at an age younger than 45. Our study supports the recommendation of regular upper GI endoscopy surveillance for LS patients beginning no later than at the age of 30. Abstract : What's new? Risk of gastric cancer (GC) is significantly increased among patients with Lynch syndrome (LS). GC screening in LS patients, however, is fraught with uncertainty, particularly regarding the use of esophagogastroduodenoscopy (EGD). The authors of this study investigated the use of EGD for regular GC surveillance in a German cohort of LS patients. Regular surveillance by EGD resulted in more frequent diagnosis and significant down‐staging of GC, relative to detection via symptoms alone. In most cases, family history of GC was negative. This study supports recommendations for regular gastroscopic surveillance in LS patients starting by age 30.